A Statistical Analysis of Students' Attitudes Towards Statistics: A Case Study of Undergraduate Bachelor of Science Students at the University of Fort Hare. (1st August 2016) - Mutambayi, R.M.; Odeyemi, A.S.; Ndege, J.O.; Mjoli, Q.T.; Qin, Y.
Abstract: Students of science disciplines at Fort Hare University must take a course in statistics along with other courses offered in their own disciplines. The goal of this study is to evaluate the general attitude of enrolled science students towards statistics module at the beginning and at the conclusion of a statistics module. Thus, to achieve the goals pursued through this study, a strategy of looking for set pre-test and post-test questionnaires was used by investigators at the beginning and the conclusion of the module. Although the learners did demonstrate moderate anxiety towards the course, anxiety anyway as compared to the beginning of the course increased by twelve percent at the conclusion of the module. In addition, a significant negative swap in their attitudes regarding the resolution of assignments in the groups was also noticed amongst the students at the end of the study. The use of real examples and the characteristics of the instructor as a factor that can help change their attitude positively towards statistics course have also been reported by students.